Species compositions mediate biomass conservation: The case of lake fish communities. Issue 3 (4th February 2022) - Arranz, Ignasi; Fournier, Bertrand; Lester, Nigel P.; Shuter, Brian J.; Peres‐Neto, Pedro R.
Abstract: Environmental and geographical factors are known to influence the number, distribution, and combination of species that coexist within ecological communities. This, in turn, should influence ecosystem functions such as biomass conservation, or the ability of a community to sustain biomass from small to large organisms. We tested this hypothesis by assessing the role of environmental factors in determining how biomass is conserved in over 600 limnetic fish communities spread across a broad geographic gradient in Canada. Comprehensive and accurate information on water conditions and community characteristics such as taxonomy, abundance, biomass, and size distributions were used in our assessment. Results showed that species combinations emerge as one of the main predictors of biomass conservation among the effects of individual species and abiotic factors. Our study highlights the strong role that geographic patterns in the distribution of species can play in shaping key ecosystem functions, with consequences for ecosystem services such as the provision of harvestable fish biomass.